(563) Long Term Growth of A Developing Economy النمو طويل الأمد للاقتصاد النامي - Qayoum, A. (INP, 2024)
Long-Term Growth of a Developing Economy. Most modern growth models are based on assumptions more relevant to developed economies, which are characterized by relatively stable savings rates and settled production technologies. In such economies, assuming constant savings rates and capital-output ratios is often justified. However, these assumptions are unsuitable for developing economies. For an economy to be classified as "developing," two key aspects are necessary: Increasing Capital Accumulation Rates: This requires a rising savings rate. Optimal Resource Utilization: This entails continual changes in production techniques, making a constant capital-output ratio unlikely except by chance. Due to these characteristics, conventional growth models are not well-suited for explaining or supporting the long-term growth of developing economies.